Stress changing analysis in structures with account of the erection level - Mkrtychev, O.V.; Andreev, M.I.; Sidorov, D.S. (Stroitelʹnaâ mehanika inženernyh konstrukcij i sooruženij (Online), 2018)
The article shows the results of computational studies of buildings taking into account and without taking into account the stages of erection. They make it possible to establish the dependence of the parameters of the stress-strain state of the load-bearing structures of a high-rise building during the calculation. The construction process is multi-stage and is strongly associated with the consistency of the work performed on the construction site. When calculating without taking into account the stage of construction in the columns of the upper floors of buildings and constructions, sufficiently large tensile forces may occur, there are characteristic horizontal deviations of the building’s axis from the vertical. The sources of distortions may be the irregularity of the rigidities of the building in the plan and the uneven deformation of the base of the structure. This phenomenon is due to the lack of staging of the erection of structures, it is believed that the building is loaded the instantly. The horizontal displacements of the floors below the installation level of the corresponding stage must be compensated, taking them into account when calculating. In this regard, the article discusses the impact of accounting for the stages of construction on the forces arising in the elements of the building. The example of calculation of a high-rise building in the software complex LIRA 9.6 taking into account the stages of construction and step-by-step application of the load on the design model. Modeling of the erection process makes it possible to take into account the uneven precipitation of vertical elements, the displacement of characteristic points (marks) of the structure in the horizontal direction.